Library automation in transitional societies : lessons from Eastern Europe - Lass, Andrew; Quandt, Richard E. (Oxford University Press, 2000)
This is a collection of papers from a 1997 conference that attempted to assess the Andrew W. Mellon Foundation's efforts to modernize Eastern European libraries after the fall of communism. Looking primarily at Hungary, Poland, the Czech Republic, and Slovakia, the international panel of contributors cover library automation, library policy, and management strategy.